Studi Karakteristik Kualitatif Dan Kuantitatif Kerbau Lumpur Di Kecamatan Kampar - Yendraliza Yendraliza (Jurnal Peternakan Indonesia (Indonesian Journal of Animal Science), 2007)
The aim of the present work was to study the physical characteristics of swamp buffalo population in Kampar sub district, Riau province. Thirty buffalos which were distributed in 5 villages (Kampar, Padang Mutung, Pulau Rambai, Panyasauan, and Batu Belah) were selected by Multi Stage Stratified Cluster Purposive Sampling Method. The selected animals which were consisted of 15 males and 15 females were observed for physical performance and measured for some body parameters. Physical performances observed and body parameters measured included: horn form; color of hair, skin and foot: form of foot and udder; body length, thorax circle, shoulder high, shoulder circle, thorax high and scrotum circle. The quantitative data were tabulated for calculation of means and standard deviation. It was found that about 83,3 % of buffalo population had horn with wider form, 72,3 % hair color of blackish grey, 61,2 % skin color of blackish gray, 100 % foot color of grey, 100 % foot form of well built foot and 100 % udder form of symmetric. The body measurement data reflected that the body development of the buffalo in Kampar closely related to their original population in India.